X-ray Computed Tomography of Structures in Opalinus Clay from Large Scale to Small Scale after Mechanical Testing. Issue 1 (1st December 2016) - Zacher, Gerhard; Kaufhold, Annette; Halisch, Matthias
Abstract : In recent years use of X-ray Computed Tomography (CT) has become more common for geoscientific applications and is used from the um-scale (e.g. for investigations of micro-fossils or pore scale structures) up to the dm-scale (full drill cores or soil columns). In this paper we present results from CT imaging and mineralogical investigations of an Opalinus Clay core on different scales and different regions of interest, emphasizing especially the 3D evaluation and distribution of cracks and fractures and their impact upon mechanical testing of such material. Enhanced knowledge of the behaviour of the Opalinus Clay as a result of these tests is of great interest, especially since this material is considered for a long term radioactive waste disposal and storage facility in Switzerland. Hence, results are compared regarding the mineral (i.e. phase) contrast resolution, the spatial resolution, and the overall scanning speed. With this extensive interdisciplinary top-down approach it has been possible to characterize the general fracture propagation in comparison to mineralogical and textual features of the Opalinus Clay. Additionally, and to the best of our knowledge, a so called mylonitic zone has been observed for the first time in an experimentally deformed Opalinus sample. The multi-scale results are in good accordance with data from naturally deformed Opalinus Clay samples, which allows systematic analysis under controlled laboratory conditions. Accompanying 3D imaging greatly enhances the capability of data interpretation and assessment of such material.